2015
DOI: 10.1088/1612-2011/12/12/125002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pump excited state absorption and its impact on laser efficiency

Abstract: Abstract. Excited state absorption (ESA) is a process that occurs in many laser gain media and can significantly impact their efficiencies of operation. In this work we develop a model to quantify the effect of ESA at the pump wavelength on laser efficiency, threshold and heating. In an analysis based on the common end pumped laser geometry we derive solutions and analytical expressions that model the laser behaviour. From these solutions we discuss the main parameters affecting efficiency, such as the laser c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…It has been previously shown that with just pump ESA (σ 1a = 0) the heating fraction is η H = (1 − η q η p ) [15], which continues to be valid when laser GSA is included by using Eq. 20 for η p .…”
Section: Appendix B: Heating Fractionmentioning
confidence: 74%
See 1 more Smart Citation
“…It has been previously shown that with just pump ESA (σ 1a = 0) the heating fraction is η H = (1 − η q η p ) [15], which continues to be valid when laser GSA is included by using Eq. 20 for η p .…”
Section: Appendix B: Heating Fractionmentioning
confidence: 74%
“…Previous models for Alexandrite have been for flashlamp pumped systems [3,4], but the efficiency of energy transfer from the pump to gain medium was not calculated leaving pump ESA unquantified. A theory has been developed for a four level end-pumped laser with pump ESA [15], but this is only applicable to Alexandrite in the spectral lasing region where laser ESA and GSA is negligibly small (approximately 760 nm to 780 nm).…”
Section: Introductionmentioning
confidence: 99%
“…• Analysis of pump excited state absorption and its impact on laser efficiency-a model to quantify the effect of excited state absorption at the pump wavelength on laser efficiency, threshold and heating is developed [6].…”
Section: • Enhanced Random Lasing From a Colloidal Cdse Quantum Dot-rmentioning
confidence: 99%
“…On top of these, excited state absorption also exists in the pumping wavelength region of Alexandrite [31]. The effect of pump excited state absorption on pumping efficiency has been discussed in [14,32,33]; and its temperature dependence is investigated in [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, the progress has been relatively slow especially for the development of ultrashort pulse laser/amplifier sources, and there is currently a need for better understanding of Alexandrite laser gain media, for accurate modeling of its laser potential. Recent detailed work by Kerridge-Johns et al on the effect of pump and laser excited state absorption on laser performance has been an important step towards this aim [14,32,33]; however, efforts in this direction face a challenge due to the limited availability of spectroscopic data. For a laser design engineer, a thorough modeling of laser dynamics and its potential as an efficient laser requires detailed knowledge of wavelength and temperature dependence of all the relevant cross sections (σ em , σ esa , and σ a ) as well as the temperature dependence of fluorescence lifetime (τ F ).…”
Section: Introductionmentioning
confidence: 99%